Treatment Outcomes and Associated Factors among Tuberculosis Patients in Southwest Ethiopia - Abebe, Tigist; Angamo, Mulugeta (Gülhane Tip Dergisi, 2015)
The aim of this study is to assess treatment outcome and associated factors among tuberculosis patients in Southwest Ethiopia. A five year general retrospective cohort was employed. Data were collected from patients’ follow up record and analyzed using SPSS version 16.0(Chicago: SPSS Inc., 2007). P-value 0.05 was considered statistically significant. In the multivariate logistic regression model, age range of (35-44.9 years (AOR=6.5, 95% CI: 3.2-13.4),45-54.9 years (AOR=12.4,95% CI: 5.9- 26.2),55-64.9 years (AOR=26.9, 95% CI:11.3-64.2) and ≥65 years (AOR=25.93, 95% CI: 6.9-98.3); male gender (AOR=2.9, 95% CI: 1.9-4.5); rural residence (AOR=3.07, 95% CI: 2.08-4.53);being at prison(AOR=2.67,95% CI: 1.11-6.37);retreatment with antituberculosis medications (AOR=1.9, 95% CI: 1.25-2.89);smear negative tuberculosis (AOR=6.7,95% CI: 4.2-10.7); extra-pulmonary tuberculosis (AOR=5.2, 95% CI: 3.1- 8.7); TB-HIV co-infected patients without co-trimoxazole preventive therapy (AOR=58.6, 95% CI: 6.7-507.8); TB-HIV co-infected patients without antiretroviral treatment(AOR=10.5, 95% CI: 1.4-77.5) were identified as independent risk factors for poor treatment outcomes in the current study. Treatment outcome among tuberculosis patients was satisfactory in the study area. Male gender, age greater than 35 years, smear negative and extra-pulmonary tuberculosis, retreatment with anti-tuberculosis medications, rural residence, being at prison, TB-HIV co-infection without co-trimoxazole preventive therapy and antiretroviral therapy were known to be independent predictors of poor treatment outcomes.